The influence of technological skills and geographical conditions on elementary school teachers’ readiness for implementing DL - Persada, Yuris Indria Persada; Oktarianto, M. Luthfi; Wibowo, Sigit; Ai, Kirana (Universitas Kanjuruhan Malang, 2025)
This study examines the influence of technological skills and geographical conditions on the pedagogical readiness of elementary school teachers in Situbondo, Indonesia, to implement deep learning approaches. Using an explanatory quantitative design, data were collected from 30 teachers across three geographic zones through a validated Likert-scale questionnaire. The analysis revealed that both variables jointly had a significant effect on pedagogical readiness (R² = 0.424; p < 0.05), although only technological skills had a significant partial influence. This suggests that teachers with better digital competence tend to be more prepared, regardless of infrastructural challenges. The findings highlight the importance of TPACK-based training and digital pedagogical support, particularly in under-resourced areas. Recommendations include strengthening teacher capacity through targeted professional development and providing contextual offline learning materials. This research contributes to understanding how technology readiness can promote equitable learning opportunities in geographically diverse regions.